Religious Context of Volunteerism in Professional Medical Ethics (Eurasian Journal of Religious Studies, 2025)
This study explores the religious context of volunteering in professional medical ethics as one of the key foundations for shaping moral and humanistic orientations in contemporary society. The purpose of the research is to identify the historical and worldview-based roots of medical volunteering and to justify its role in strengthening deontological principles, professional culture, and the physician’s moral responsibility. Special attention is given to the analysis of religious traditions that have influenced the formation of medical ethics, as well as to the practices of professional medical volunteering in both historical and modern contexts. The scientific and practical significance of the work lies in its demonstration of the mechanisms through which spiritual values and professional competencies are integrated, showing how religious worldviews and the culture of compassion provide a solid basis for the development of medical volunteering. The methodological framework of the study relies on historical-philosophical and comparative analysis, which makes it possible to trace the evolution of ethical foundations in medicine and to examine the dialectical relationship between religion, medicine, and social processes. The results of the research reveal that volunteering in medicine, rooted in religious notions of mercy, altruism, and compassion, has played a significant role in the development of medical deontology. Various historical and modern examples of professional volunteering are presented, illustrating its effectiveness in fostering social trust and solidarity. The value of the research lies in the systematization of the religious-ethical foundations of medical volunteering and their impact on shaping the moral law in the physician’s consciousness. The practical importance of the study is reflected in the potential application of its findings for the development of educational programs in medical universities, the strengthening of deontological principles, and the cultivation of a professional culture among future physicians.Keywords: medical volunteers, worldview, morality, ethics, religion